2017
DOI: 10.1111/ijfs.13601
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioaccessibility of ergocalciferol in nanoemulsion‐based delivery system: the influence of food‐grade emulsifiers with different stabilising mechanisms

Abstract: Summary The effect of emulsifier type on the in vitro bioaccessibility of ergocalciferol‐loaded nanoemulsions was examined (mouth, stomach and small intestinal phases). Oil‐in‐water nanoemulsions were prepared using emulsifiers with different stabilising mechanisms: decaglycerol monooleate (MO7S; steric), modified lecithin (ML; electrostatic), sodium caseinate (SC; electrosteric) and ML‐MO7S (combined electrostatic and steric). The droplet size, size distribution, ζ‐potential and microstructure of nanoemulsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…After centrifugation, samples were separated into three phases: a thin oil phase on top, a transparent micellar phase in the middle, and a sediment phase at the bottom. 40,46 Fucoxanthin was assumed to be solubilized in the micellar phase. The extracted fucoxanthin from the raw digesta phase and micellar phase was collected and passed through a PTFE syringe filter (0.45 μm).…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation, samples were separated into three phases: a thin oil phase on top, a transparent micellar phase in the middle, and a sediment phase at the bottom. 40,46 Fucoxanthin was assumed to be solubilized in the micellar phase. The extracted fucoxanthin from the raw digesta phase and micellar phase was collected and passed through a PTFE syringe filter (0.45 μm).…”
Section: Methodsmentioning
confidence: 99%
“…Increased bioavailability of vitamin D encapsulated in O/W NE prepared by ultrasonication technique showing a droplet size 300−450 nm and shelf life >90 days in simulated gastrointestinal tract was reported by Walia et al (2017). The ergocalciferol in vitro bioaccessibilities in O/W NEs prepared using emulsifiers with different stabilizing mechanisms were comparable for decaglycerol monooleate (62%; steric mechanism), modified lecithin (64%; electrostatic mechanism) or their combination (65%) but they were significantly higher than that estimated for SCas emulsifier (12%; electrosteric) and also the free fatty acids release rate in the small intestinal phase was the lowest for SCas (Shu et al 2018). Folic acid nanoencapsulated by double emulsions having an internal NE composed of W/O system with folic acid present in the water phase and reemulsified within an aqueous phase of pectin−whey protein concentrate complexes showed EE about 88.3%, whereby EE was predominantly affected by the dispersed phase content of double NE and surfactant had the minimum influence (Assadpour et al 2016).…”
Section: Vitamin Nanoemulsionsmentioning
confidence: 69%
“…Ozturk, Argin, Ozilgen, and McClements (2014) also showed that lecithin NE exhibited some instability when subjected to high ionic strength and low pH. Similarly, other authors demonstrated that lecithin NE particle size increased after the gastric phase (Chang & McClements, 2016;Shu et al, 2018). Regarding SLN and NLC, both presented a particle size increase (p > 0.05) after the gastric phase from 145.3 ± 4.64 nm to 489.1 ± 215.11 nm and from 173.3 ± 7.52 nm to 524.5 ± 168.2 nm, respectively.…”
Section: Size ζ-Potential and Morphologymentioning
confidence: 79%